Improving Teller’s motivation at Joint stock Commercial Bank for Investment and Development of Viet Nam (BIDV) - SGD1 branch - Nguyễn, Thu Trang (2020)
Aims of researchFor the above research rationale, there are some main objectives the thesis should cover as follows: To clarify the theories of motivation, then propose the most appropriatemotivation model. To analyze and find out strengths and weaknesses of tellers’ motivation at BIDV–Transaction Center 1. To propose recommendations for improving motivation for tellers at BIDV–Transaction Center 1